2021
DOI: 10.1021/acs.jpcc.1c03417
|View full text |Cite
|
Sign up to set email alerts
|

Nickel/Molybdenum Bimetallic Alloy for Dry Reforming of Methane: A Coverage-Dependence Microkinetic Model Simulation Based on the First-Principles Calculation

Abstract: Ni-based catalysts have attracted much attention because of their high catalytic activity for dry reforming of methane (DRM) reaction and their low-cost characteristics. The deactivation caused by carbon deposition has become a major factor restricting its application. Mo doping is expected to improve the carbon deposition resistance of Ni-based catalysts. In this study, we used density functional theory (DFT) calculations and the microkinetic model to compare the catalytic activity of Ni and MoNi4 (as a Mo-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 68 publications
2
16
0
Order By: Relevance
“…Right: Reaction rate of CO 2 with temperature. Reprinted with permission from ref . Copyright 2021, American Chemical Society.…”
Section: Design Strategies Synthesis Approaches and Mechanisms Of Ni-...mentioning
confidence: 99%
See 1 more Smart Citation
“…Right: Reaction rate of CO 2 with temperature. Reprinted with permission from ref . Copyright 2021, American Chemical Society.…”
Section: Design Strategies Synthesis Approaches and Mechanisms Of Ni-...mentioning
confidence: 99%
“…Wang et al used DFT and the microkinetic model to compare MDR activities of Ni and MoNi 4 catalysts (Figure III) . The results showed that intermediates were more strongly adsorbed on the MoNi 4 catalyst than on the Ni catalyst, which was associated with the stronger electron-donating capacity in the former due to Mo doping.…”
Section: Design Strategies Synthesis Approaches and Mechanisms Of Ni-...mentioning
confidence: 99%
“…Wan-Ying et al performed DFT calculations on DRM mechanisms of Ni and a Ni–Mo alloy. They showed that the activation of CH 4 and CO 2 is higher in the Ni–Mo compared to monometallic Ni . Turap et al tested a series of Co–Ni catalysts with different ratios .…”
Section: Co2 Utilization For Hydrocarbon and Lower Olefin Productionmentioning
confidence: 99%
“…29 Moreover, Wang et al pointed out that the MoNi 4 (001) surface can improve the coke resistance by more efficient CH 4 and CO 2 activation. 30 However, there have been few detailed studies of electronic properties on the role of Mo (or Mo–O) in Ni–Mo catalysts for coke resistance, namely, how the Mo (or Mo–O) species achieve the activity and the carbon resistance.…”
Section: Introductionmentioning
confidence: 99%